Floristic Composition and Carbon Storage of Floor Vegetation in Community Forests of Ciamis Regency, West Jawa - Sumarna, Ardi; Hadisusanto, Suwarno; Purnomo (Institut Pertanian Bogor (IPB University), 2024)
Agroforestry-integrated community forests foster greater plant diversity compared to conventional agriculture, potentially offering significant ecological and societal benefits. However, the specific contribution of diverse floor vegetation within these forests to carbon cycling remains understudied. This study addresses this knowledge gap by comprehensively analyzing the floristic composition and carbon storage potential of floor vegetation in tropical community forests. Using a stratified random sampling design with quadrats to ensure representative data collection across various locations in Ciamis Regency, West Java, Indonesia, we identified 296 plant species belonging to 89 families. Our analysis revealed that the understory vegetation exhibits moderate species diversity and stores carbon ranging from 0.107 to 0.238 Mg C ha⁻¹, with an average sequestration potential of 0.730 Mg C ha⁻¹. These findings suggest that community forests harbor diverse floor vegetation communities with significant carbon storage and sequestration potential, providing valuable insights for environmentally sustainable community forest management and contributing to broader efforts towards climate change mitigation.